Anti-inflammatory activity of Nigella sativa oil in rats - Abdul Kadir, Arifah; Cheng, K. S.; Mohd Johari, Azlina; Ahmad, Zuraini (Veterinary Association Malaysia, 2004)
Nigella sativa (N. sativa), commonly known as black seed, has been a well known herb since ancient times with a wide range of healing properties. The aim of this study was to investigate anti-inflammatory activity of N. sativa seed oil at three dosages on carrageenan-induced paw oedema, total white blood cell (TWBC) count and plasma protein in rats. Acute inflammation was induced by subplantar injection of carrageenan (0.1 ml, 1 % w/v) into the rat hind paw. 500 mglkg, 1000 mg/kg and 1500 mg/kg of N. sativa oil were administrated orally. Paw oedema, total white blood cell count and plasma protein were assessed. N. sativa seed oil exerted significant inhibition of paw oedema at the dosage of 1500 mg/kg at second hour and plasma protein at a dosage of 1000 mg/kg at third hour (p< 0.05). No significant inhibition ofTWBC count was exerted by N. sativa seed oil at third hour after treatment at dosages used in this study. There was also dose-dependent correlation of N. sativa seed oil on inhibition of paw oedema. These results support the traditional use of N. sativa seed oil for the treatment of inflammatory diseases.